Degradation behavior and mechanism of polymer films for high-ohmic resistor protection in a heat and humid environment. (February 2016) - Wang, X.Y.; Zhang, H.; Ma, X.P.; Cheng, Q.; Li, C.G.; Li, M.X.; Chen, T.N.; Zhang, P.; Shao, J.Q.
Abstract: The protection of polymer films is critical to the reliability of high-ohmic resistors working in a heat and humid environment, and temperature is the main factor resulting in failure of coated resistors. However, in this study hydrogen evolution reaction (HER) and corrosion reaction of OH − ions are found to be another two important factors determining the fate of coated resistors. When temperature effects can be neglected, corrosion resulted from OH − ions generated in HER may be the major reason of polymer degradation, the mechanism of which is discussed based on the polymer films mainly formed by phenolic and epoxy resins. Highlights: Performance of coated high-ohmic resistors in heat and humid resistance was studied. Polymer films for resistor protection are mainly formed by phenolic and epoxy resins. Hydrogen evolution reaction (HER) can occur on polymer film for a working resistor. Corrosion resulted from OH − ions generated in HER may lead to polymer degradation.